2020
DOI: 10.1002/ange.202003500
|View full text |Cite
|
Sign up to set email alerts
|

Mutant‐Selective Allosteric EGFR Degraders are Effective Against a Broad Range of Drug‐Resistant Mutations

Abstract: Targeting epidermal growth factor receptor (EGFR) through an allosteric mechanism provides a potential therapeutic strategy to overcome drug‐resistant EGFR mutations that emerge within the ATP binding site. Here, we develop an allosteric EGFR degrader, DDC‐01‐163, which can selectively inhibit the proliferation of L858R/T790M (L/T) mutant Ba/F3 cells while leaving wildtype EGFR Ba/F3 cells unaffected. DDC‐01‐163 is also effective against osimertinib‐resistant cells with L/T/C797S and L/T/L718Q EGFR mutations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…An in vitro cell permeability experiment confirmed that the antiproliferative activity of the PROTAC was dependent on the ligand inhibitory activity and cell permeability. Further, the degradation and antiproliferative activity potentiated with the combination of osimertinib, which concluded that the combination therapy of EGFR-TKI with PROTAC might be an effective strategy in future cancer treatment . In this rapidly growing EGFR-PROTACs development journey, autophagy mediated degradation of EGFR further added a new direction in the targeted protein degradation field.…”
Section: Egfr Protacs As a Novel Therapeutic Modalitymentioning
confidence: 98%
See 3 more Smart Citations
“…An in vitro cell permeability experiment confirmed that the antiproliferative activity of the PROTAC was dependent on the ligand inhibitory activity and cell permeability. Further, the degradation and antiproliferative activity potentiated with the combination of osimertinib, which concluded that the combination therapy of EGFR-TKI with PROTAC might be an effective strategy in future cancer treatment . In this rapidly growing EGFR-PROTACs development journey, autophagy mediated degradation of EGFR further added a new direction in the targeted protein degradation field.…”
Section: Egfr Protacs As a Novel Therapeutic Modalitymentioning
confidence: 98%
“…151 In addition, 25a precursor (94) was synthesized by amination with 72 by the free amino group of the PEG linker (92). 160 Further, these precursor molecules (90 and 94) were coupled with EGFR inhibitors (91 and 24) to yield the corresponding PROTACs (16 and 25a) (Figure 15).…”
Section: Synthesis Of Protacs Through E3lmentioning
confidence: 99%
See 2 more Smart Citations
“…Second- and third-generation TKIs such as afatinib (BIBW-2992), , rociletinib (CO-1686), , WZ-4002, and osimertinib (AZD-9291) target the more drug-resistant variant L858R/T790M EGFR by irreversibly alkylating a conserved active site cysteine side chain (C797). Monoclonal antibodies and small molecules that interact directly with EGFR can also be engineered to induce EGFR degradation via either proteasomal or lysosomal pathways.…”
mentioning
confidence: 99%